Knowledge of açaí handlers before and after educational action on the triggering factors of chagas disease in the municipality of Ponta de Pedras - Pará (Research, Society and Development, 2022)
Chagas disease (CD) is an infectious disease, also known as American trypanosomiasis, chaguism or, as it is popularly called, “grown heart disease”. It is caused by the flagellate protozoan Trypanosoma cruzi, whose vector is a hematophagous triatomine. In Brazil, chronic cases of the disease predominate due to contamination from past decades, but in 2006, the country received international certification of interruption of vector transmission. Currently, the oral route is the main route of transmission through the ingestion of contaminated food (sugarcane juice, açaí, bacaba, among others). The objective of this study was to verify the knowledge of açaí handlers before and after an educational action on the triggering factors of Chagas disease in the municipality of Ponta de Pedras in the State of Pará, in addition to tracing their sociodemographic profiles. This is a descriptive research with an exploratory nature and a qualitative approach through the analysis of sociodemographic and cultural aspects, in the patterns of responses of açaí handlers. As well as a quantitative approach through data collection. Ten açaí handlers were interviewed, of which 50% have only completed high school, in terms of age, 50% are between 37 - 46 years old and 30% have an average of 20 - 29 years in the profession. A lack of knowledge about CD was also detected for the performance of their functions before the educational action. It was found that after the training there was an improvement in knowledge and even an interest in future training on the subject. It is then concluded that the planning of training or updates through lectures or other strategies, aimed at these workers could minimize underreported cases and even the most serious cases of the disease, thus avoiding an overload on the health services in the region and a better endemic control.